De Sara Waters a Josey Aimes: representações sobre a violência contra as mulheres em narrativas fílmicas (final do século XX - início do século XXI) - Miranda, Pedro Henrique (2017)
The main purpose of this work is to analyse the way hollywood film industry builds representations on violence against women in their productions from the end of 20th century to beginning of 21st century. Therefore, our study focus on the relation between cinema and representation, it means that we tried to reflect about the representational nature of cinema. For this purpose, initially we guided ourselves mostly in Roger Chartier’s perspective that points to representation as the product resulting from the practice.The full-length films are inserted in the esthetic configurations of the New Hollywood post 1975, with narratives that run from the late 1980s through the mid-2000s. In these productions, violence against women takes place in different spaces, both in the private and in the public environment, being commited mainly by marital partners, strangers and co- workers. The feature films also present the physical, psychological and sexual violence marks in the daily life of these women who seek ways to end up these abusive relationships. The presented films belong to Stalker Movies and Courtroom Movies, two different Hollywood film styles. Stalker Movies are characterized by having the victims persecution in their stories, while the Courtroom Movies approach narratives related to the United States judicial system. Four sources were chosen for the analysis intention: The Accused – 1988, Sleeping with the Enemy – 1991, Enough – 2002 and North Country – 2005.